2005
DOI: 10.1007/s00192-005-1309-2
|View full text |Cite
|
Sign up to set email alerts
|

Transobturator SAFYRE sling is as effective as the transvaginal procedure

Abstract: Introduction: SAFYRE is a monofilament polypropylene mesh held between two self-anchoring silicone columns that associates universal approach with readjustability. This unique feature allows for comparing two different approaches, i.e., transvaginal and transobturator, using the same sling. Materials and methods: A total of 226 patients with clinical and urodynamic diagnosis of SUI underwent SAFYRE sling procedure, which was performed either by transvaginal (group 1; 126 patients) or transobturator approach (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 9 publications
0
28
0
2
Order By: Relevance
“…Ulmsten and Petros ¢rst introduced the TVT Neurourology and Urodynamics DOI 10.1002/nau Kuuva and Nilsson [2002] 1,455 patientsTVT 24/367 6 transfusion/signif bleed (0.4%), 11 bladder perforations (0.75%), 2 vascular injury (0.1%)1 nerve injury (0.07%), 4 abscesses (0.2%) Hong et al [2003] 375 patients, TVT 5/143 1 nerve injury (0.3%), 4 hematoma (1.1%) Kobashi and Govier [2003] 140 patients, SPARC 6/6 4 transfusions (2.8%), 1 bowel perforation (0.7%), 1 hematoma (0.7%) Karram et al [2003] 350 patients, TVT 6/97 2 hematoma (0.9%), 3 nerve injury (0.9%), 1urethral erosion (0.3%) Abouassaly et al [2004] 241 patients, TVT 7/173 6 signi¢cance bleed >500 ml (2.5%), 1 hematoma (0.4%) Levin et al [2004] 313 patients, TVT 2/67 2 unrecognized blad perf (0.6%) Wang [2004] 600 patients, TVT 0/28 Tsivian et al [2004] 200 patients, TVT 1/25 1 unrecognized blad perf (0.5%) Hodro¡ et al [2005] 445 patients, SPARC 2/82 1 bowel perforation (0.2%), 1 rectus hematoma (0.2%) Hammad et al [2005] 1,459 patients, TVT 993, SPARC 466 2/121 2 urethral erosion (0.1%) Paick et al [2005] 274 patients, TVT 0/110 De Leval [2003] 107 patients, TO generic (inside-out) 0/7 Delorme et al [2004] 32 patients, Uratape 0/8 DeTayrac et al [2004] 30 patients, Uratape 1/8 1 obturator hematoma (3%) Costa et al [2004] 183 patients, Uratape 2/20 2 urethral erosion (1%) Mellier et al [2004] 94 patients, Monarc 0/3 Domingo et al [2005] 65 patients, Uratape 43, Obtape 21 1/10 1 obturator abscess (1.5%) Fischer et al [2005] 220 patients, Monarc, Serasis-TO 0/18 Spinosa and Dubuis [2005] 117 patients, ObTape 0/10 Naidu et al [2005] 96 patients, Monarc 0/12 Siegel [2005] 30 patients, ObTape 1/6 1 obturator abscess (3%) Palma et al [2005] 100 patients, SAFYRE 0/20 Krauth et al [2005] 604 patients, I-STOP 1/60 1 signi¢cant bleed (0.2%) Davila et al [2005] 200 patients, Monarc 0/13 Roumeguere et al [2005] 120 patients, Uratape 60, Obtape 60 2/38 2 unrecognized urethra inj (1.7%)…”
Section: Discussionmentioning
confidence: 99%
“…Ulmsten and Petros ¢rst introduced the TVT Neurourology and Urodynamics DOI 10.1002/nau Kuuva and Nilsson [2002] 1,455 patientsTVT 24/367 6 transfusion/signif bleed (0.4%), 11 bladder perforations (0.75%), 2 vascular injury (0.1%)1 nerve injury (0.07%), 4 abscesses (0.2%) Hong et al [2003] 375 patients, TVT 5/143 1 nerve injury (0.3%), 4 hematoma (1.1%) Kobashi and Govier [2003] 140 patients, SPARC 6/6 4 transfusions (2.8%), 1 bowel perforation (0.7%), 1 hematoma (0.7%) Karram et al [2003] 350 patients, TVT 6/97 2 hematoma (0.9%), 3 nerve injury (0.9%), 1urethral erosion (0.3%) Abouassaly et al [2004] 241 patients, TVT 7/173 6 signi¢cance bleed >500 ml (2.5%), 1 hematoma (0.4%) Levin et al [2004] 313 patients, TVT 2/67 2 unrecognized blad perf (0.6%) Wang [2004] 600 patients, TVT 0/28 Tsivian et al [2004] 200 patients, TVT 1/25 1 unrecognized blad perf (0.5%) Hodro¡ et al [2005] 445 patients, SPARC 2/82 1 bowel perforation (0.2%), 1 rectus hematoma (0.2%) Hammad et al [2005] 1,459 patients, TVT 993, SPARC 466 2/121 2 urethral erosion (0.1%) Paick et al [2005] 274 patients, TVT 0/110 De Leval [2003] 107 patients, TO generic (inside-out) 0/7 Delorme et al [2004] 32 patients, Uratape 0/8 DeTayrac et al [2004] 30 patients, Uratape 1/8 1 obturator hematoma (3%) Costa et al [2004] 183 patients, Uratape 2/20 2 urethral erosion (1%) Mellier et al [2004] 94 patients, Monarc 0/3 Domingo et al [2005] 65 patients, Uratape 43, Obtape 21 1/10 1 obturator abscess (1.5%) Fischer et al [2005] 220 patients, Monarc, Serasis-TO 0/18 Spinosa and Dubuis [2005] 117 patients, ObTape 0/10 Naidu et al [2005] 96 patients, Monarc 0/12 Siegel [2005] 30 patients, ObTape 1/6 1 obturator abscess (3%) Palma et al [2005] 100 patients, SAFYRE 0/20 Krauth et al [2005] 604 patients, I-STOP 1/60 1 signi¢cant bleed (0.2%) Davila et al [2005] 200 patients, Monarc 0/13 Roumeguere et al [2005] 120 patients, Uratape 60, Obtape 60 2/38 2 unrecognized urethra inj (1.7%)…”
Section: Discussionmentioning
confidence: 99%
“…Only one randomized trial 14 and six out of the eleven cohort studies 5,20,25,26,29,30 reported data on reoperation secondary to long-term voiding dysfunction. Overall this outcome was rare and therefore numbers were insufficient to pool results.…”
Section: Voiding Dysfunction Requiring Reoperationmentioning
confidence: 99%
“…Palma et al 18 compared the efficacy of different Safyre surgical techniques, and did not detect any difference in terms of the cure rates, which were 92.1% using the suprapubic vaginal approach and 94% using the transobturator approach. However, the transobturator technique offered reduced time in the operating theatre and a lower rate of complications such as bladder perforation (2.3% and 0%, respectively) and postoperative urgency (20.6% and 10%, respectively).…”
Section: Discussionmentioning
confidence: 99%